Climate change in human history prehistory to the present - Lieberman, Benjamin 1962- (Bloomsbury Academic, an imprint of Bloomsbury Publishing Plc, 2018)
"Climate Change and Human History provides an up-to-date and concise introduction to the relationship between human beings and climate change throughout history. Starting with periods hundreds of thousands of years ago and continuing up to the present day, the book illustrates how natural climate variability affected early human societies, and how humans are now altering climate drastically within much shorter periods of time. For each major period of time, the book will explain how climate change has created opportunities as well as risks and challenges for human societies. The book introduces and develops several related themes including: Phases of climate and history; factors that shape climate; climate shocks and sharp climate shifts; climate and the rise and fall of civilizations; industrialization and climate science; [and] accelerating climate change, human societies, and the future. An ideal companion for all students of environmental history, Climate Change and Human History clearly demonstrates the critical role of climate in shaping human history and of the experience of humans in both adapting to and shaping climate change."--Publisher's description.